Composite Membrane Based on Graphene Oxide Sheets and Nafion for Polymer Electrolyte Membrane Fuel Cells. (29th October 2014) - Wang, Liang; Kang, Junmo; Nam, Jae-Do; Suhr, Jonghwan; Prasad, Ajay K.; Advani, Suresh G.
Abstract : A composite membrane for fuel cell applications was prepared by incorporating custom-made graphene oxide (GO) in Nafion resin. The GO was used to provide mechanical reinforcement to Nafion. Transmission electron microscopy confirmed the formation of highly crystalline and individually-dispersed graphene oxide sheets. Tensile strength, water uptake, swelling, proton conductivity and electrical conductivity of the composite membranes were measured and compared with pure Nafion. The polarization curves indicated that the fuel cell performance of the 3wt% GO/Nafion composite membrane was similar to that of the pure Nafion membrane, but the composite membrane was superior to Nafion in terms of mechanical properties.